Physiological characterization of Escherichia coli rpoB mutants with abnormal control of ribosome synthesis. - Little, R (1983)
We have previously reported the isolation of Escherichia coli rpoB mutants in which the control of ribosome synthesis by the nucleotide effector guanosine tetraphosphate (ppGpp) is altered, owing to a 20-fold increased sensitivity of the mutant RNA polymerases to ppGpp. In these mutants, the level of ppGpp during exponential growth is decreased about 10-fold, relative to that of rpoB+ wild-type strains, such that a near normal partitioning of RNA polymerase occurs with respect to stable RNA (rRNA and tRNA) gene activity. Here, the physiological effects of two different rpoB alleles in a relA+ and relA background were analyzed in greater detail by comparison with their isogenic rpoB+ wild-type parents. For a given growth medium, the rpoB mutations were found to affect four parameters which resulted in a reduction of growth rate. The results reinforce a previous conclusion that a key element in control of the bacterial growth rate is a mutual relationship between control of ribosome synthesis by ppGpp and control of relA-independent ppGpp metabolism by the concentration and function of ribosomes.